1999
DOI: 10.1177/00912709922011728
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Gender or Age on Binding Characteristics of Valproic Acid to Serum Proteins in Pediatric Patients with Epilepsy

Abstract: The gender- and age-related binding characteristics of valproic acid to serum proteins were determined in the pediatric population. Serum samples examined in the study were obtained from 61 pediatric patients (28 males, 33 females) with epilepsy on valproic acid monotherapy. Their ages ranged from 1 to 15 years (mean age with [SD]: 7.8 [3.9] years; < 10 years, n = 41; > or = 10 years, n = 20). The in vivo population binding parameters of valproic acid to serum proteins and theoretical minimal unbound serum fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…The relationship between the total and unbound concentrations of VPA was altered in the case of patients treated with ethosuximide combination therapy or polytherapy (Table 2). The population means of B m (130·0 ÎŒg/mL, or 0·90 m m ) and K d (7·8 ÎŒg/mL, or 54 ÎŒ m ) calculated by taking account of this alteration are comparable with the reported values of 0·75–1·24 m m ( B m ) and 36–91 ÎŒ m ( K d ) (15, 16, 19, 22).…”
Section: Discussionsupporting
confidence: 82%
“…The relationship between the total and unbound concentrations of VPA was altered in the case of patients treated with ethosuximide combination therapy or polytherapy (Table 2). The population means of B m (130·0 ÎŒg/mL, or 0·90 m m ) and K d (7·8 ÎŒg/mL, or 54 ÎŒ m ) calculated by taking account of this alteration are comparable with the reported values of 0·75–1·24 m m ( B m ) and 36–91 ÎŒ m ( K d ) (15, 16, 19, 22).…”
Section: Discussionsupporting
confidence: 82%
“…Free VPA fraction decreased significantly as serum albumin concentration increased in both groups (Figures 1a and 2a), and free VPA concentration increased non‐linearly depending on the total VPA concentration in both groups (Figures 1b and 2b). This is consistent with previous reports [25–27] . These results suggest that both serum albumin and total VPA concentration have to be considered to predict the protein‐binding characteristics of VPA.…”
Section: Discussionsupporting
confidence: 93%
“…23,24) As shown in Table 4, the parameter Kd was determined not to be related to the physical development of the infants. Such a property of the parameter Kd was also observed in various studies previously reported, 10,25) and these results can be interpreted to reflect the fact that the serum albumin concentration in infants increases according to their physical development, while the protein-binding affinity of VPA is little affected by the physical development. 20,21) However, an additional investigation may be necessary to clearly explain that the protein-binding affinity in infants is not affected by the physical development, since it has been reported for various compounds that the protein-binding affinity to albumin decreases in infants, due to increased plasma concentrations of endogenous substances, including bilirubin and fatty acids.…”
Section: Fig 2 Simulated Relationship Profiles Between the Total Ansupporting
confidence: 79%
“…In fact, there have been several studies on the estimation and/or a regression equation to predict the unbound from the total concentration. [9][10][11] However, as revealed in our previous study, the equation for epileptic children or adult patients is not applicable for epileptic infants aged less than 1 year old. The unbound serum VPA concentrations in infants vary patient by patient more markedly than those in children, and, thereby, their total and unbound VPA concentrations are poorly correlated (Fig.…”
mentioning
confidence: 81%